The immature stages and female imago of Rheocricotopus (Psilocricotopus) sirventorum Andersen & Mendes, 2012, a Neotropical member of the chalybeatus species group (Diptera, Chironomidae, Orthocladiinae) - Pinho, Luiz Carlos; Andersen, Trond (Zootaxa, 2023)
The female, larva and pupa of Rheocricotopus (Psilocricotopus) sirventorum Andersen & Mendes, 2012, are described based on specimens collected in southern Brazil. The species is the sole described species of Rheocricotopus Brundin, 1956 from the Neotropical region. The subgeneric placement is confirmed, based on the morphology of the female, larva and pupa. The species belongs in the chalybeatus species group, and a key to the pupae of the group is presented.